"I am not a Lady, I am a Scientist." Chemistry, Women, and Gender in the Enlightenment and the Era of Professional Science. (3rd July 2022) - Serrano, Elena; Mercelis, Joris; Lykknes, Annette
Abstract : This article introduces a collection of papers on women, gender, and chemistry in eighteenth- and twentieth-century Europe and the United States. After briefly surveying previous research on women and gender in science and outlining the long history of women in chemistry, we present this special issue's main findings concerning several key themes, including the identities and strategies of women engaged in chemical activities and the enabling circumstances and networks that helped these women gain entry into male-dominated institutions and fields of study. We suggest that these overarching themes are equally relevant to the Enlightenment era and the late nineteenth- and early to mid-twentieth-century age of professional science, thus illustrating the benefits of jointly treating cases that might otherwise seem to have little in common.